2006
DOI: 10.1080/15287390500360133
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Tissue Distribution of Orally Administered Trichloroethylene in Male and Female Rats: Identification of Glutathione- and Cytochrome P-450-Derived Metabolites in Liver, Kidney, Blood, and Urine

Abstract: Male and female Fischer 344 rats were administered trichloroethylene (TRI) (2, 5, or 15 mmol/kg body weight) in corn oil by oral gavage and TRI and its metabolites were measured at times up to 48 hr in liver, kidney, blood, and urine. We tested the hypothesis that sex-dependent differences in distribution and metabolism of TRI could help explain differences in toxicity. Higher levels of TRI were generally observed in tissues of males. A biphasic pattern of TRI concentration was observed in liver, kidney, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
3

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
3
33
3
Order By: Relevance
“…Maximal rates of TCE oxidative metabolism in rodents also differ between males and females. For example, Lash et al [53] found higher concentrations of CYP-derived metabolites of TCE ( i.e ., CH, TCA, TCOH) in livers of males than in females; the opposite pattern, however, was observed in kidneys. These results are consistent with higher maximal rates of CYP-dependent metabolism and overall metabolic clearance of TCE in male rats.…”
Section: Cyp-dependent Oxidation Of Tcementioning
confidence: 99%
“…Maximal rates of TCE oxidative metabolism in rodents also differ between males and females. For example, Lash et al [53] found higher concentrations of CYP-derived metabolites of TCE ( i.e ., CH, TCA, TCOH) in livers of males than in females; the opposite pattern, however, was observed in kidneys. These results are consistent with higher maximal rates of CYP-dependent metabolism and overall metabolic clearance of TCE in male rats.…”
Section: Cyp-dependent Oxidation Of Tcementioning
confidence: 99%
“…Humans exposed to relatively low levels of TRI by inhalation (i.e., 100 ppm) transiently exhibit as high as 50 μM concentrations of the GSH conjugate of TRI, S-(1,2-dichlorovinyl)glutathione (DCVG), in the plasma [35] and rats exposed to TRI by oral gavage exhibit renal cortical concentrations of DCVC as high as 50 pmol/g tissue [36]. These data suggest that under typical environmental exposure conditions (< 5 ppb), even the lowest concentration of DCVC that was tested (i.e., 1 μM) would be high.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, NA-DCVC can be deacetylated by AA3-which is highly expressed in the renal proximal tubule, liver, and brain-to generate S-1,2-dichlorovinyl-L-cysteine (DCVC) (2) and further transformed via β-lyases or flavin monooxygenases into lethal products capable of causing acute renal failure and toxicity to the liver and brain. (4,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Thus, inhibition of AA3 can decrease DCVC formation and ameliorate TCE toxicity, presenting a potential target for drug discovery.…”
mentioning
confidence: 99%